2014
DOI: 10.1149/06122.0035ecst
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Activiation of Sr3Fe2O7 Electrocatalysts for Water Oxidation at Neutral pH

Abstract: The Ruddlesden-Popper-type layered perovskite strontium ferrite (Sr3Fe2O7) was studied as an electrocatalyst for water oxidation to molecular oxygen (O2). The electrocatalytic activity of Sr3Fe2O7 was found to be dependent on the temperature, and the overpotential for water oxidation was markedly lower at 70 oC than at 30 oC. Namely, at pH 7, O2 evolution initiated with overpotentials of approximately 100 and 300 mV at 70 and 30 oC, respectively. When lanthanum-substituted Sr3Fe2O7, Sr2.6La0.4Fe2O7, was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…They found that CaCu 3 Fe 4 O 12 had superior activity to state-of-the-art catalysts such as RuO 2 and Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3‑δ . In addition, we demonstrated that the availability of Fe 4+ significantly affected OER activity of strontium ferrite (Sr 3 Fe 2 O 7 ) derivatives, which contain Fe 4+ but suffer from charge disproportionation (2Fe 4+ → Fe 3+ + Fe 5+ ) at room temperature . When we suppressed the consumption of Fe 4+ owing to this reaction by increasing the temperature or introducing a dopant element, its OER activity considerably increased.…”
Section: Resultsmentioning
confidence: 93%
“…They found that CaCu 3 Fe 4 O 12 had superior activity to state-of-the-art catalysts such as RuO 2 and Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3‑δ . In addition, we demonstrated that the availability of Fe 4+ significantly affected OER activity of strontium ferrite (Sr 3 Fe 2 O 7 ) derivatives, which contain Fe 4+ but suffer from charge disproportionation (2Fe 4+ → Fe 3+ + Fe 5+ ) at room temperature . When we suppressed the consumption of Fe 4+ owing to this reaction by increasing the temperature or introducing a dopant element, its OER activity considerably increased.…”
Section: Resultsmentioning
confidence: 93%
“…Sr 3 Fe 2 O 7 and SrFeO 3 powders were synthesized by a solid-state reaction using α-iron oxide and strontium carbonate as precursors ( 33 , 34 ). A stoichiometric mixture of α-iron oxide (α-Fe 2 O 3 , Shanghai Aladdin Biochemical Technology Co., Ltd., 99.8%) and strontium carbonate (SrCO 3 , Bide Pharmatech Ltd., 99%) was fully ground and spread out in an alumina crucible.…”
Section: Methodsmentioning
confidence: 99%
“…So far, most of the studies focusing on strontium ferrites have used one material alone, viz. SrFeO3- [4,14] or Sr3Fe2O7- [15,16]. In this study, we propose a simple preparation method that results in a mixture of the two perovskite phases.…”
Section: Introductionmentioning
confidence: 99%